Combination or single-agent chemotherapy as adjuvant treatment of gastric cancer: A systematic review and meta-analysis of published trials. (February 2016) - Iacovelli, Roberto; Pietrantonio, Filippo; Maggi, Claudia; de Braud, Filippo; Di Bartolomeo, Maria
Highlights: This meta-analysis showed a survival benefit of polychemotherapy over single agent as adjuvant treatment of gastric cancer. A prospective randomized trial is needed in high-risk patients. Treatment personalization in the clinical practice must take into account disease risk features and patients conditions. Abstract: Background: Chemotherapy is standard care in resected gastric cancer (GC). Despite the evidence that combination chemotherapy (CT) increases overall survival (OS) as compared to single agent therapy in metastatic disease, no study proved this benefit in the adjuvant setting. We performed a systematic review and meta-analysis based on trial data on the role of combination over single agent CT as adjuvant treatment of GC. Methods: MEDLINE/PubMed and Cochrane Library were searched for randomized phase III trials that compared combination vs. single agent CT in patients treated with radical surgery for non-metastatic GC. Data extraction was conducted according to the PRISMA statement. Statistical analyses were conducted to calculate the summary hazard ratio (HR) for OS and disease free survival (DFS) and 95% Confidence Intervals (CIs) by using random-effects or fixed effects models based on the heterogeneity of included studies. A subgroup analysis was performed in patients treated with D2 lymphadenectomy. Results: A total of 3572 patients were available for this analysis, 1857 received D2 lymphadenectomy, and fluoropyrimidine was given in 97% of patients of the control arm. In the overall population, the combined therapy decrease the risk of death by 13% (HR = 0.87; 95%CI, 0.79–0.95; p  = 0.004) with fixed effect and by 19% (HR = 0.81; 95%CI, 0.68–0.97; p  = 0.02) with random effect; significant heterogeneity was found. When analysis was limited to studies that required D2 lymphadenectomy a significant reduction of the risk of death was found in favor of combination CT (HR = 0.86; 95%CI, 0.76–0.98; p  = 0.02). In the 3487 patients valuable for DFS, combination CT decreased the risk of relapse by 23% (HR = 0.77; 95%CI, 0.70–0.84; p  < 0.001) with fixed effect and by 27% (HR = 0.73; 95%CI, 0.49–1.09; p  = 0.12) with random effect; significant heterogeneity was found. Conclusions: This analysis reported that adjuvant combination CT decreases the risk of death over single agent therapy in patients with non-metastatic GC.